Penggunaan Media Loose Part Dalam Mengembangkan Aspek Kognitif Anak Usia Dini - Siti Badriyah, Euis; Hibana; Hamid Samiaji, Mukhamad (Jurnal Tumbuh Kembang Anak Usia Dini, 2023)
One of the potential developments of early childhood is the cognitive development of children, and loose part is a media material for teaching a use in children's learning is never ending, loose part teaching materials can be used as a tool to explore various aspects including; Problem solving, Creativity, Concentration, Fine motoric, Gross motoric, Science, Language development (Literacy), Art (Art), Mathematical thinking logic (math), Engineering (Engineering) and Technology (Technology). The purpose of this research is to develop cognitive aspects of early childhood through freelance teaching materials. The method used in this research is Classroom Action research. The results of the Class Action research at PAUD Nurul Hidayah Garut, the ability of 10 children in developing their cognitive obtained in Cycle I was considered less than optimal so that improvements were needed in Cycle II. In Cycle II there was an increase in the child's ability in fine motor development according to the expected target, so this research was stopped in Cycle II.